An Overview of the Burden of Non- Communicable Diseases in India - R Prakash Upadhyay (Tehran University of Medical Sciences, 2012)
Non-communicable disease continues to be an important public health problem in India, being responsible for a major proportion of mortality and morbidity. Demographic changes, changes in the lifestyle along with increased rates of urbanization are the major reasons responsible for the tilt towards the non-communicable diseases. In India, there is no regular system for collecting data on non-communicable diseases (NCDs) which can be said to be of adequate coverage or quality. Lack of trained health care workers, primary care providers armed with inadequate knowledge and skills along with ill-defined roles of various health sectors i.e. public, private, and voluntary sectors in providing care have played key hurdles in combating the growing burden of non-communicable diseases. Empowerment of the community through effective health education, use of trained public health personnel along with provision of free health care and social insurance would prove beneficial in effectively controlling the growing prevalence of NCDs.